Evaluation of Quality of Service on Megavision Internet Services Provider in Jelekong Village Using Speedtest by Ookla - Rusdan, Muchamad (PPM Telkom University, 2024)
This research aims to test the Quality of Service (QoS) on the internet service provider Megavision in Jelekong Village, Baleendah District, Bandung Regency using Speedtest by Ookla Mobile. Measurement methods include download speed, upload speed, throughput, latency (ping), jitter, and packet loss. The research results show that the Megavision Provider can provide relatively good quality internet services, with an average download speed of 19.10 Mbps, an average upload speed of 19.78 Mbps, average throughput of 38.886 kbps in the